0203 The lung burden of Asbestos Fibres (AF) and Asbestos Bodies (AB) and the risk of mesothelioma (MM) for exposures ceased 30 years ago. (23rd June 2014) - Merler, Enzo; Girardi, Paolo; Luigi Barbieri, Pietro; Bressan, Vittoria; Benedetta Somigliana, Anna
Abstract : Objectives: To estimate the risk of MM according to AF and AB in the lungs. Method: Freeze dried lung samples from 309 MM and 41 controls have been analysed for AF (Scanning Electronic Microscopy) and AB (Optical Microscopy) from subjects investigated and classified for probability and circumstances of asbestos exposure. Odds Ratios (OR) were obtained using logistic regression. Results: 254 (82%) MMs have been classified as occupationally and 25 (8%) as non-occupationally exposed: Geometric Mean (GM) for AF burden was 1 950 000 and 608 000 ff/g dlt, respectively; and 39 300 and 3300 for AB. 75% and 58% of the AF respectively were amphibole. Controls reported a GM of 269 000 AF and 28 of AB g/dlt. For any increase of 100.000 ff/g dlt, we computed an OR of 1.7 (1.3–2.3) for amphibole, 1.1 (1.0–1.3) for chrysotile, among occupational MMs; an OR of 1.3 (1.0–1.7) and 1.1 (1.0–1.1) among non-occupational MMs. The 1997 Helsinki criteria for attribution to occupational exposure would have excluded more than 30% of MMs under study: here occupational exposures ceased on average 26 years before the disease, and therefore clearance and time since last exposure must be taken into account because are relevant determinants of the retained amount of fibres. Conclusions: The risk of MM increases with the amount of retained amphibole, and to a lesser extent, of chrysotile fibres. Because occupational and non-occupation asbestos exposures have been to mixture of fibres, the lungs of MM patients are still loaded with amphibole AF.